Analisis Faktor Yang Memengaruhi Tindakan Tidak Aman Pada Pekerja Ketinggian Proyek 6 Ruas Tol Dalam Kota Jakarta Seksi 1a Kso Jaya Konstruksi-Adhi Tahun 2021 - Bagas Suryo Prayogo (2021)
A construction project is an activity with high risks and can cause several problems, either for the environment or humans around the project site. In its process, accidents caused by unsafe actions can occur. In January 2021, 12 (twelve) reports of penalties were found due to workers committing unsafe acts, out of 12 penelties there was 1 (one) accident case. Age, years of service, knowledge, workload and supervision have been notable to be risk factors of unsafe actions. Therefore, this study aims to analyze factors that can influence unsafe actions on height workers at project 6 of Inner-City Toll Roads in Section 1A Operational Cooperation of Jaya Konstruksi-Adhi in 2021. The type of study used quantitative analytic with a cross-sectional design, this study uses the chie square test. The population of the study was 150 workers, with the samples used were 120 workers with accidental sampling collection technique. This study was conducted from May 2021 to June 2021. The result in this study showed that 44,2% of workers took unsafe action. Research results Knowledge (p-value < 0.001), Workload (p-value < 0.018), Supervision (p-value 0.001) have a significant relatinship. Therefore, it is recommended for companies to increase supervision and training for workers who have a high risk of danger, and advice to workers is to get enough rest.